SOVEREIGNTY AT STAKE: BALANCE-OF-THREAT AND THE INSTITUTIONAL DESIGN OF THE MALACCA STRAITS PATROL, 2004–2025 - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna; Nadine Rizqi Auliya; Mochammad Sirojuddin Afandy (FISIPOL UM Sumbar, 2026)
This article analyzes the establishment and sustained operation of the Malacca Straits Patrol (MSP) through a structural realist framework, drawing on balance-of-threat theory and defensive realism. The central question asks why the littoral states of the Malacca Strait established and maintained sovereignty-constrained military cooperation against piracy, and what causal mechanisms explain both the form and the limits of that cooperation. Employing within-case process tracing and structured content analysis of official documents, incident databases, and diplomatic records across three threat-level phases (2004–2025), the study traces a causal mechanism from dual threat escalation piracy surpassing economic tolerance thresholds and extra-regional intervention signals generating sovereignty anxiety through balance- of-threat alignment to sovereignty-constrained cooperative security. The findings demonstrate that the MSP’s institutional architecture is not a design failure but a theoretically predicted outcome: states cooperated at precisely the institutional depth that captured security benefits without incurring sovereignty costs. The study contributes a formally specified realist explanation for a case dominated by liberal and descriptive accounts, extends balance-of-threat theory from inter-state military alliances to cooperative responses against non-traditional security threats, and identifiesquot;sovereignty-constrained cooperationquot; as a theoretically predictable institutional modality under defensive realism.